Increasing Productivity and Competitiveness of Cute Cake and Bakery Padang MSMEs - Nurfatiha Pasya Salsabilla; Rika Rohim; Lia Astrilina; Vika Wahyuni; Lusiana Lusiana (Eduvest - Journal of Universal Studies, 2025)
MSMEs play an important role in the Indonesian economy, including in the culinary sector such as Comel Cake and Bakery in Padang. However, challenges in increasing productivity and competitiveness are obstacles that must be overcome so that businesses can survive and grow. This study aims to analyze the strategies implemented by Comel Cake and Bakery in increasing operational efficiency, product innovation, and digital- based marketing in order to face industry competition. The method used is a qualitative approach with interview techniques, observation, and literature studies related to MSME management. The results of the study show that increasing productivity is carried out through optimizing the production process, employee training, and using quality raw materials at efficient costs. Meanwhile, the strategy to increase competitiveness involves product diversification, strong branding, and utilizing social media and e-commerce to reach a wider market. In addition, support from the government and the MSME community also contributes to accelerating business growth. By implementing this strategy, Comel Cake and Bakery is able to increase production volume, expand market share, and obtain greater profits. This study provides insight for MSME actors in adopting the right strategy to increase competitiveness in the digital era. Therefore, synergy between innovation, technology, and supporting policies is the main key in encouraging the sustainability and growth of MSMEs in the culinary sector.